Some lithodid crabs (Crustacea: Decapoda: Lithodidae) from Taiwan and adjacent waters, with the description of one new species from Guam - Macpherson, Enrique; Chan, Tin-Yam (Zootaxa, 2008)
Seven species of Lithodid crabs were collected during cruises off Taiwan and Guam. One new species, Lithodes paulayi is described and illustrated. Neolithodes nipponensis, Lithodes sp., Paralomis arae, P. dofleini and P. truncatispinosa are reported from these islands for the first time, extending the distributional range in each case. Lithodes paulayi closely resembles L. longispina Sakai, 1971, from off Japan and the central Pacific, but can be differentiated by the branchial region possessing two long dorsal spines and only one long marginal spine, whereas L. longispina has only one long dorsal spine, situated at level of cardiac spines, and two long marginal spines. The description of a juvenile of P. arae Macpherson, 2001, is also included.